2019
DOI: 10.1177/2374289519859841
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in Histological Assessment of Mitotic Activity Between Microscopy and Digital Whole Slide Images Informs Conversion for Clinical Diagnosis

Abstract: Validating digital pathology as substitute for conventional microscopy in diagnosis remains a priority to assure effectiveness. Intermodality concordance studies typically focus on achieving the same diagnosis by digital display of whole slide images and conventional microscopy. Assessment of discrete histological features in whole slide images, such as mitotic figures, has not been thoroughly evaluated in diagnostic practice. To further gauge the interchangeability of conventional microscopy with digital disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…Most studies comparing LM and WSI obtained MC using 400Â magnification images (image resolution: 0.25 mm/pixel). 3,13,32,64 For MCs obtained from canine melanomas, WSI at 400Â or 200Â magnification had similar inter-and intraobserver concordance with one another and with LM. 64 Based on published information as well as personal experiences among the authors, diagnostic evaluation and MC can be readily performed with WSI.…”
Section: Wsi Validation For Diagnosis and MCmentioning
confidence: 75%
See 2 more Smart Citations
“…Most studies comparing LM and WSI obtained MC using 400Â magnification images (image resolution: 0.25 mm/pixel). 3,13,32,64 For MCs obtained from canine melanomas, WSI at 400Â or 200Â magnification had similar inter-and intraobserver concordance with one another and with LM. 64 Based on published information as well as personal experiences among the authors, diagnostic evaluation and MC can be readily performed with WSI.…”
Section: Wsi Validation For Diagnosis and MCmentioning
confidence: 75%
“…There is generally good agreement between WSI and light microscopy (LM) with regard to cytologic and histologic diagnosis and MC in animal and human tumors. 2,3,13,16,18,29,32,48,53,64 A better correlation was observed in cases with higher MCs as compared to those with lower MCs. 3 Some studies reported a trend toward underestimating the MC with WSI as compared to LM and attributed this to difficulty of identifying MF via WSI.…”
Section: Wsi Validation For Diagnosis and MCmentioning
confidence: 87%
See 1 more Smart Citation
“…Notably, a central pathologist revision of cases was not available, so the accuracy of histological diagnosis could be biased. 27 Also, SEER classified UTUC with grading from I to IV, whereas the most recent WHO classification and current guidelines classify low-grade and high-grade tumors. 28 Another limitation is the absence of information regarding further treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the presence of preoperative hydronephrosis 21 or inflammation, 22 the impact of preoperative and postoperative ureteroscopy, 23,24 and tumor architecture 25,26 are all factors that could be associated with prognosis, but we were not able to account for them. Notably, a central pathologist revision of cases was not available, so the accuracy of histological diagnosis could be biased 27 . Also, SEER classified UTUC with grading from I to IV, whereas the most recent WHO classification and current guidelines classify low‐grade and high‐grade tumors 28 .…”
Section: Discussionmentioning
confidence: 99%